Potential Therapies for Infectious Diseases Based on Targeting Immune Evasion Mechanisms That Pathogens Have in Common With Cancer Cells - Wong, Jodi; Choi, Stephen Yiu Chuen; Liu, Rongrong; Xu, Eddie; Killam, James; Gout, Peter W.; Wang, Yuzhuo (Frontiers in Cellular and Infection Microbiology, 2019)
Many global infectious diseases are not well-controlled, underlining a critical need for new, more effective therapies. Pathogens and pathogen-infected host cells, like cancer cells, evade immune surveillance via immune evasion mechanisms. The present study indicates that pathogenic bacteria, endoparasites, and virus-infected host cells can have immune evasion mechanisms in common with cancers. These include entry into dormancy and metabolic reprogramming to aerobic glycolysis leading to excessive secretion of lactic acid and immobilization of local host immunity. The latter evasion tactic provides a therapeutic target for cancer, as shown by our recent finding that patient-derived cancer xenografts can be growth-arrested, without major host toxicity, by inhibiting their lactic acid secretion (as mediated by the MCT4 transporter)-with evidence of host immunity restoration. Accordingly, the multiplication of bacteria, endoparasites, and viruses that primarily depend on metabolic reprogramming to aerobic glycolysis for survival may be arrested using cancer treatment strategies that inhibit their lactic acid secretion. Immune evasion mechanisms shared by pathogens and cancer cells likely represent fundamental, evolutionarily-conserved mechanisms that may be particularly critical to their welfare. As such, their targeting may lead to novel therapies for infectious diseases.